Hemispheric and Seasonal Contrast in Cloud Thermodynamic Phase From A‐Train Spaceborne Instruments. Issue 6 (22nd March 2021) - Villanueva, Diego; Senf, Fabian; Tegen, Ina
Abstract: Aerosol‐cloud interactions are an important source of uncertainty in current climate models. To understand and quantify the influence of ice‐nucleating particles in cloud glaciation, it is crucial to have a reliable estimation of the hemispheric and seasonal contrast in cloud top phase, which is believed to result from the higher dust aerosol loading in boreal spring. For this reason, we locate and quantify these contrasts by combining three different A‐Train cloud‐phase products for the period 2007–2010. These products rely on a spaceborne lidar, a lidar‐radar synergy, and a radiometer‐polarimeter synergy. We show that the cloud‐phase from the product combination is more reliable and that the estimation of the hemispheric and seasonal contrast has a lower error compared to the individual products. To quantify the contrast in cloud‐phase, we use the hemispheric difference in ice cloud frequency normalized by the liquid cloud frequency in the southern hemisphere between −42 °C and 0 °C. In the midlatitudes, from −15 to −30 °C, the hemispheric contrasts increase with decreasing temperature. At −30 °C, the hemispheric contrast varies from 29% to 39% for the individual cloud‐phase products and from 52% to 73% for the product combination. Similarly, in the northern hemisphere, we assess the seasonal contrast between spring and fall normalized by the liquid cloud frequency during fall. At −30 °C, the seasonal contrast ranges from 21% to 39% for the individual cloud‐phase products and from 54% to 75% for the product combination. Plain Language Summary: The influence of atmospheric particles on clouds is one of the main unknowns in climate predictions. Particularly, the cloud glaciation process and its dependence on desert dust and soot particles are not well‐understood. To better understand the differences in cloud glaciation between hemispheres, we counted liquid and ice cloud tops, as observed from four different satellites, during 4 years. Combining these observations, we could confirm a higher frequency of ice cloud tops during spring in the northern hemisphere. We found that the contrast between hemispheres is higher than previously thought. These results will help to improve our understanding of cloud glaciation processes, which can be valuable for future climate predictions and for understanding the impact of aerosols on radiation and precipitation. Key Points: A satellite product ensemble was used to locate and quantify the hemispheric and seasonal contrast in cloud top thermodynamic phase At −30 °C, half of the liquid cloud tops observed in the southern hemisphere would glaciate in the northern hemisphere The new product ensemble is more reliable than the individual products and suggests a previous underestimation of the cloud‐phase contrasts